SOCIAL CARE FOR DOGS – LACLIMPA: AN EXPERIENCE REPORT - Carlos, Júlia Larissa Lima; Matos, Ana Carolina dos Santos; Carneiro, Rodrigo Lima (Seven Editora, 2026)
The present study, characterized as an experience report in university extension, aims to describe the experience of members of the Academic League of Small Animal Internal Medicine – LACLIMPA, in the development of a veterinary social care project aimed at dogs owned by guardians in situations of socioeconomic vulnerability. Activities are carried out weekly at the veterinary teaching clinic of the State University of Bahia (UNEB), Campus IX, in the municipality of Barreiras, and are conducted by undergraduate students under the direct supervision of the faculty member responsible for the Small Animal Internal Medicine area. The project targets low-income communities, including guardians duly registered in the Unified Registry for Federal Government Social Programs (CadÚnico), ensuring greater equity and social targeting of the extension action. Clinical consultations, basic examinations, outpatient procedures, and guidance on vaccination, sanitary management, animal welfare, and responsible ownership are provided. In addition to expanding access to animal health care for vulnerable populations, the initiative contributes to the prevention of zoonoses and to the promotion of the One Health concept. From an academic perspective, the project enables students to develop technical and ethical competencies, integrating theory and practice in a real professional context. Thus, the social care provided by LACLIMPA constitutes an extension activity of social, academic, and educational relevance, strengthening the university tripod of teaching, research, and extension, while promoting animal welfare and the social responsibility of the veterinarian in training.DOI: https://doi.org/10.56238/sevened2025.036-152